Effect of temperatures on TSA in cement mortars under electrical field. (20th February 2018) - Zeng, Qianpu; Wang, Chong; Luo, Yaoling; Yu, Chao; Huang, Qian; Luo, Chaoqun
Highlights: The deterioration of mortars exposed to different temperatures was studied. The damage of mortars under electrical field was more severe than immersed specimens. Electrical field accelerated the thaumasite form of sulfate attack (TSA). Thaumasite was detected after 120 d under electrical field at low temperatures. Abstract: This study was aimed to investigate the effect of temperatures on thaumasite form of sulfate attack (TSA) in cement mortars under electrical field. The mortars were preserved at −5 °C, 5 °C, 20 °C, 5 °C–20 °C cycles, respectively. The damages were visually observed and compressive strengths of specimens were tested on a regular basis. X-ray diffraction (XRD) and Fourier Transform Infrared Spectroscopy (FTIR) were carried out to analyze deteriorated products. The results indicated that the specimens at 20 °C under both full-immersion and electrical field after 150 days were rarely damaged and thaumasite could not be detected. The failure of specimens at −5 °C was mainly due to freezing-thawing and salt scaling, resulting superficial damage. Moreover, an electrical field accelerated the damage induced by sulfate attack in the mortars and the deterioration of specimens at 5 °C was mostly due to the formation of TSA.